Implementasi Sistem Kendali Proposional Integral Derivatif (PID) pada Porototype Pendeteksi Brightness Cahaya Ruangan - Masyitah Aulia; Kurniawati Kurniawati; Paris Ali Topan; Titi Andriani; Desi Maulidyawati (Prodi Ilmu Komputer Universitas Bumigora, 2022)
PID control is used in the tool to determine the accuracy of a combined system with the feedback characteristics of the system, based on the error values ​​obtained from the Kp, Ki, and Kd values ​​that respond to the dimmer. The dimmer functions to adjust the brightness of the lamp, then it will be controlled by Arduino UNO. This experiment is devoted to testing P, PD, PI, and PID control as practicum learning modules in the electrical engineering study program, at the Sumbawa University of Technology. This controlled trial obtained 200 recorded data with the same set point value of 2 and in a very fast time of 200 seconds. P control with increased or decreased Kp value resulted in 10% system stability, PI control with increased Kp and Ki values ​​resulted in 20% system stability whereas when Kp value was increased and Ki decreased the system was unstable. PD control does not get stable system performance at all. PID control with increased Kp and Ki values, and lowered Kd values ​​resulted in 75% successful system stability, whereas when Kp and Kd were increased, Ki values ​​were lowered resulting in 50% system stability. So in this study, the PID control would be very suitable to be used as a control that stabilizes system performance.